Neurochemical Evidence of Preclinical and Clinical Reports on Target-Based Therapy in Alcohol Used Disorder - Prajapati S.K.; Bhaseen S.; Krishnamurthy S.; Sahu A.N. (My University, 2025)
Abstract: Alcohol use disorder (AUD) is a chronic relapsing disorder, which enforces a person to compulsively seek alcohol, restricting control over alcohol intake leads to emergence of an undesired emotional state during abstinence. There are recent advances for better understanding of neurocircuitry involved in the pathophysiology of AUD. Alcohol interaction with neuronal membrane proteins results in changes in neuronal circuits. It is also linked with the potential medication and their clinical validation concerning their pharmacological targets for alcoholic abstinence. This review covers research work from the past few decades on the therapeutic advances on treatment of alcohol dependence; further detailing the fundamental neurochemical mechanisms after alcohol administration. It also covers interaction of alcohol with GABAergic, glutaminergic, dopaminergic, serotonergic and opioid systems. This review further elaborated the neurobiology of noradrenergic, cholinergic and cannabinoid systems and their interaction with AUD. Elaborative information of potential drug targets under current exploration for AUD treatment with their mechanisms are reported here along with clinical outcomes and the associated side effects. Graphic Abstract: [Figure not available: see fulltext.] © 2020, Springer Science+Business Media, LLC, part of Springer Nature.